Biotic controls on post-glacial floodplain dynamics in the Colorado Front Range - Pilgrim, Lina Eleonor Polvi, author; Wohl, Ellen, advisor; Rathburn, Sara, committee member; Merritt, David, committee member; Bledsoe, Brian, committee member (Colorado State University. Libraries, 2011)
A recent surge in ecogeomorphic research has shed light on the numerous feedbacks and couplings between physical and biotic processes in developing geomorphic and ecologic process and form. Recent work has shown the critical importance of vegetation in altering overall channel form and developing meandering channel systems. This dissertation expands on planform classifications and the understanding of biotic-physical couplings through examining two components of post-glacial floodplain evolution in broad headwater valleys in the Colorado Front Range. First, I evaluate the role of beaver in Holocene floodplain evolution in low-gradient, broad headwater valleys to understand the historical range of variability of sedimentation processes and to determine the role of beaver in altering channel complexity and how that contributes to spatial heterogeneity of sedimentation processes. These objectives were carried out in Beaver Meadows and Moraine Park in Rocky Mountain National Park through analysis of subsurface sediment, geomorphic mapping, and aerial photography analyses. Second, I examine the role of various riparian species in stabilizing streambanks in order to determine the relative importance of bank versus root characteristics in stabilizing streambanks and to develop a functional classification of riparian vegetation in stabilizing streambanks. Data for this portion of the project were collected in three study sites along an elevation gradient in the Colorado Front Range: Phantom Canyon on the North Fork Poudre River (1920 m), North Joe Wright Creek (3000 m), and Corral Creek (3100 m), all of which are located in the Cache la Poudre drainage. For fourteen species (4 trees, 3 shrubs, 3 graminoids, and 4 herbs), root tensile strength, root size distribution, and root morphology were characterized. Streambank geometry and stratigraphy from Moraine Park were combined with vegetation characteristics in a physically-based bank stability model to determine the role of various physical bank characteristics and root characteristics in stabilizing streambanks. Examination of Holocene sedimentation processes in these broad, low-gradient headwater valleys, which are fairly disconnected from their hillslopes, lends support to the beaver-meadow complex hypothesis that uses beaver dams as the mechanism to explain the accumulation of fine sediment in glacial valleys. In the study valleys, sediment associated with beaver dams account for a significant (30-50%) portion of the relatively thin alluvium overlaying glacial till and outwash. Sedimentation rates were temporally and spatially heterogeneous across the floodplain, with higher rates associated with beaver pond sedimentation. Fluvial complexity, in terms of multi-thread channels, islands, and channel bifurcations, increases with beaver populations and number of ponds, and magnifies the potential for beaver damming because of increased channel length, which accelerates the development of fluvial complexity and valley sedimentation. Bank stability modeling determined that although bank and root characteristics are interrelated, physical bank characteristics play a larger role in determining bank stability than root characteristics. However, within similar streambank types, vegetation type is a strong predictor of overall streambank stability, and streambanks without vegetation were consistently the least stable. The presence of rhizomes, the maximum root diameter, the root tensile strength, and the lateral root extent of each species are the most important root characteristics in determining streambank stability. Riparian shrubs (willows) and riparian trees are the best streambank stabilizers. Upland trees and graminoids are mid-level bank stabilizers, and herbaceous species are mid/low-level bank stabilizers. In addition to sediment and flow regimes, the two biotic processes studied interact to form the overall channel planforms that dominate these broad headwater valleys. Assuming a relatively snowmelt-dominated flow regime and a gravel-bed channel system in the headwaters, four planform regimes are identified based on low to high beaver populations and the abundance and presence of xeric or riparian vegetation. Without beaver or bank-stabilizing vegetation, a braided channel planform will likely develop. With bank stabilizing vegetation but without a sustainable beaver population, a single-thread meandering channel will form, which only has a thin riparian vegetation strip and small fluvial influence on the overall valley ecological and geomorphic processes. With a sustainable beaver population and riparian vegetation along the streambank, a stable multi-thread channel system will form which has implications for the ecological and physical form and process of the valley. A valley with abundant beaver but little to no bank-stabilizing vegetation is impossible under natural conditions, because riparian vegetation is necessary to sustain a beaver population and their dam-building. However, a narrow, incised channel may be observed as a legacy effect from beaver removal. The probable planform regimes can be inferred over the range of Holocene climate conditions in the Colorado Front Range, and understanding of these biotic-physical interactions should be a crucial component of any management decisions for geomorphic or ecologic conditions.
Keywords: bank stability; beaver; complexity; floodplain; riparian; vegetation